Strategy in the second nuclear age : power, ambition, and the ultimate weapon - Yoshihara, Toshi; Holmes, James R. (Georgetown University Press, 2012)
A "second nuclear age" has begun in the post-Cold War world. Created by the expansion of nuclear arsenals and new proliferation in Asia, it has changed the familiar nuclear geometry of the Cold War. Increasing potency of nuclear arsenals in China, India, and Pakistan, the nuclear breakout in North Korea, and the potential for more states to cross the nuclear-weapons threshold from Iran to Japan suggest that the second nuclear age of many competing nuclear powers has the potential to be even less stable than the first. Strategy in the Second Nuclear Age assembles a group of distinguished schola.